Role of salt on adhesion of an epoxy/aluminum (oxide) interface in aqueous environments. Issue 1 (5th November 2015) - Tan, Kar Tean; White, Christopher C.; Hunston, Donald; Gorham, Justin M.; Imburgia, Michael J.; Forster, Aaron M.; Vogt, Bryan D.
Abstract : Joints held by polymeric adhesives are commonplace in many engineered products, but normal service can require exposure to environmental conditions that present a significant challenge for maintaining the structural integrity of the interface. In particular, aqueous environments can wreak havoc on the joint strength. Here, a mechanistic approach is used to understand the difference in the debonding behavior of an epoxy/aluminum (oxide) interface when exposed to deionized (DI) water and aqueous sodium chloride by correlating macroscopic failure with the sorption of salt and water into the adhesive and its nanoscale distribution. For the epoxy‐aluminum system examined here, the presence of sodium chloride increases the resistance to crack growth in comparison to DI water. The debonding appears to be controlled by water near the buried interface. Salt water decreases the solubility of water in the epoxy and decreases the concentration of water near the buried interface, but the concentration of salt that enters the epoxy is below the detection limit. Thus, even if ions cannot penetrate or sorb into the adhesive, the presence of salt can significantly alter the water distribution within the adhesive and ultimately the strength of the joint. POLYM. ENG. SCI., 56:18–26, 2016. © 2015 Society of Plastics Engineers